Bulldozers and the rubber tree - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Since the 1980s, a necrosis of unknown origin has been affecting the bark of the Hevea brasiliensis, the tree from which natural rubber is made.